Perception of undergraduate emergency medical services students about mental health - Abdullah Alruwaili; Ahmed Alanazy; Fatimah Alyousif; Kawthar Alnajjad; Asrar Alali (Emergency Care Journal)
Mental illness significantly impacts morbidity and mortality; however, research on paramedic students' perceptions and attitudes toward individuals with mental health presentations is limite. The incidence of mental disorders in Saudi Arabia is increasing, and knowledge about them would enhance the ability of the paramedics to provide more help to the population. This study evaluates the perceptions of undergraduate emergency medical students before and after completing a mental health education block. We conducted a quasi-experimental design study for forth year students who were enrolled in a mental health block and have been added to King Saud bin Abdulaziz University for Health Sciences and were asked to partake in pre- and post-subject surveys. They were requested to share their perspectives on mental health through electronic questionnaires. With a total of 83 participants, averaging 21.33 years old, from three regions in Saudi Arabia, we found significant differences in the following questions before and after the mental health block: participants became more comfortable managing mental health issues (strongly agreeing increased from 10.8% to 36.1%). Moreover, perceptions about psychosis and violence changed (from agreeing to disagreeing). Questions on racism and trauma showed a significant increase in the strongly agreeing. The majority agreed more that neglect can cause mental illness (strongly agreeing increased from 30.1% to 63.9%). Lastly, exposure to rape was significantly strongly associated with mental disorders (69.9%, P value <0.0001). Our study showed positive shifts in attitudes and increased mental health knowledge after introducing a mental health block. The block not only improved understanding but also holds promise for future paramedics in offering empathetic care. Overall, the study underscores the need for continuous mental health education in paramedic curricula for better readiness in addressing diverse population needs.